Diabetes management during and after Ramadan among pregnant women in Saudi Arabia: exploring self-efficacy, self-care, and glycemic control - Alamri, Omar Mohammed; Raposo, António; Alshaikh, Ayoub Ali; Alfheeaid, Hani A.; Alamri, Ali Mohammed; Alasmri, Mohammed Abdullah; Alwubayran, Nada Mohammed; Shukri, Ahmed Khaled; Alslamah, Thamer; Albaridi, Najla A.; Ahmad, Md Faruque; Otayf, Abdullah Y.; et al. (Frontiers in Nutrition, 2025)
BackgroundFasting during Ramadan poses distinct challenges for individuals with diabetes, especially pregnant women, due to increased metabolic demands and the heightened risk of hypoglycemia, hyperglycemia, and dehydration. Although medical guidelines often advise against fasting in this group, many women still choose to observe the fast. This study aims to explore diabetes self-efficacy and self-care behaviors during and after Ramadan among pregnant women.MethodsThis cross-sectional study was conducted during and after Ramadan 2025 at Abha Maternity Hospital in Aseer region in Saudi Arabia. Pregnant women with gestational or pre-existing diabetes were recruited. Data were collected using validated Arabic versions of the Diabetes Self-Efficacy Scale and the Summary of Diabetes Self-Care Activities questionnaire. Paired t-tests and correlation analyses were used to examine changes and relationships.ResultsA total of 162 pregnant women with diabetes participated in this study. Self-efficacy scores remained stable during and after Ramadan (mean 4.8 vs. 4.9, p = 0.2), while self-care scores declined significantly post-Ramadan (32.5 to 29.8, p = 0.001). HbA1c distribution shifted slightly, with fewer participants in the <5.7% range after Ramadan and more in the 5.7–6.4% range. Most managed diabetes using oral drugs with diet and exercise (42%). Medical education was linked to higher self-care scores (p < 0.001), while trial fasting improved self-efficacy (p = 0.001). Perceived glycemic control improved post-Ramadan (difficulty decreased from 72.8 to 65.4%, p = 0.001). Hypoglycemia caused 26.5% of fast-breaking episodes, though “other reasons” were more common. Older age and higher pregnancy order correlated with lower self-care and self-efficacy, while education and perceived health showed positive correlation.ConclusionThis study underscores the need for culturally sensitive, pregnancy-specific interventions to support safe fasting. Sustained education, individualized care, and preparation before Ramadan were linked to better outcomes, highlighting the importance of ongoing support beyond the fasting period for optimal diabetes management.